Metode Dialogis dalam Epistemologi Islam - Hasan Bakti Nasution; Roeslaini Roeslaini (AR-RASYID : Jurnal Pendidikan Agama Islam, 2021)
This study aims to describe the dialogical method in Islamic epistemology. This research uses library research method. The result of this research is that the dialogical method is an effort to explore Islamic education knowledge which is carried out through written works presented in the form of conversations (questions and answers) between two or more people based on scientifically justifiable arguments. Dialogue is divided into two, namely dialogue that is carried out personally, and dialogue that is carried out in groups. Ethics in dialogue include (1) Rabbani; (2) Humane; (3) Universal; (4) Balance; (5) Realistic. The dialogue method in the Qur'an is divided into three types of dialogue, namely: al-hiwar, al-jadal, and hujaj. The dialogue method in the hadith is like the hadith of Gabriel who asked the Prophet Muhammad. about Iamn, Islam and Ihsan. The implementation of the dialogue method in Islamic education can be applied by cultivating question and answer in the teaching and learning process.